Secondary school learners' contextualized knowledge about reflection and refraction: a case study from South Africa. Issue 2 (3rd April 2018) - John, Merlin; Molepo, Jacob Maisha; Chirwa, Max
Abstract: Background: The development of context-based science curricula has been identified as one of the most effective curricular innovations to develop interest and better conceptual understanding of many areas in science. However, such a curriculum can be more fruitful if it starts with the assessment of learners' contextualized knowledge about the science topic in hand. Purpose: The focus of this paper is to investigate secondary school learners' knowledge of the optical phenomena of reflection and refraction in relation to certain contexts. Sample: The sample for the study consisted of two Grade-11 intact groups of 70 learners in total at a selected senior secondary school in the Mthatha District of the Eastern Cape Province in South Africa. Design and methods: The study focused on exploring the learners' conceptions about the optical phenomena of reflection and refraction. The data were collected from three two-tier questions, which exposed the learners to certain contexts which could be explained using optics principles. The first tier of each question was a context-based multiple-choice question and in the second tier, the participants were asked to justify their answers to the first tier. Results: Majority of the participants failed to correctly interpret the given contexts using optics principles. Moreover, only a few learners could justify their scientifically acceptable answers with scientifically acceptable explanations. Conclusions: The participants experienced serious conceptual difficulties when they were required to apply the optics concepts in the real-world contexts presented to them. Moreover, the participants' conceptual difficulties about reflection and refraction were also found to be associated with their inability to understand correctly the optical processes involved in vision.